Variability in stigma length and apocarotenoid content in Crocus sativus L. selections of Kashmir - Raies A Qadri, J I Mir, N Ahmed, A H Wafai (Journal of Spices and Aromatic Crops, 2012)
Identification of high yielding selections using the existing gene pool of saffron shows promise and potential for improving the productivity of this crop. The present study was conducted at Srinagar (Jammu & Kashmir) with 31 saffron selections. Variations in respect to stigma length was observed. Apocarotenoid content was correlated with stigma length of saffron. Stigma size vis-a-vis quality evaluation confirmed that saffron of Kashmir is of intrinsically high quality with respect to colouring, aroma and taste. Variability in stigma characteristics observed in saffron selections can be utilized for saffron crop improvement.